Can countries rely on foreign saving for investment and economic development? - Eduardo Cavallo; Barry Eichengreen; Ugo Panizza (Graduate Institute of International and Development Studies, 2016)
A surprisingly large number of countries have been able to finance a significant fraction of domestic investment using foreign finance for extended periods. While many of these episodes are in low-income countries where official finance is more important than private finance, we also identify a number of episodes where a substantial fraction of domestic investment was financed via private capital inflows. That said, we find that foreign savings are not a good substitute for domestic savings. More often than not, episodes of large and persistent current account deficits do not end happily. Rather, they end abruptly with compression of the current account, real exchange rate depreciation, and a sharp slowdown in investment. We conclude that financing growth and investment out of foreign savings, while not impossible, is risky.
Keywords: F32; O16; 330; current account; growth; volatility; savings